Removal of carbamazepine in aqueous solutions through solar photolysis of free available chlorine. (1st September 2016) - Yang, Bin; Kookana, Rai S.; Williams, Mike; Du, Jun; Doan, Hai; Kumar, Anupama
Abstract: Removal of a persistent antiepileptic drug carbamazepine (CBZ) in aqueous solutions was investigated by using solar photolysis combined with free available chlorine (FAC). The combination of chlorination with simulated or natural sunlight markedly enhanced removal of CBZ in 10 mM phosphate buffer solution (pH 7.0) and river water (pH 7.0) compared with sunlight or FAC alone. Further analysis indicated that the observed enhancements in CBZ removal can be attributed to the in situ hydroxyl radical (HO) and ozone (O3 ) production during FAC photolysis. During 70 min simulated sunlight photolysis combined with FAC treatment, HO reaction contributed to 35.8% removal of CBZ and O3 reaction contributed to 40.6% removal, while only 5.3% of CBZ was removed by HOCl reaction. The oxidation products of CBZ, epoxide CBZ, 10, 11-dihydro-10, 11-dihydroxy CBZ, 1-(2-benzaldehyde)-4-hydro-(1H, 3H)-quinazoline-2-one (BQM), 1-(2-benzaldehyde)-(1H, 3H)-quinazoline-2, 4-dione (BQD) and 4-aldehyde-9-acridone, were mainly formed from the HO and O3 attack at the double bond on the central heterocyclic ring of CBZ. Formation of these oxidation products did not cause any increase or decrease in toxicity to microbial species tested through Microbial Assay for Toxicity Risk Assessment (MARA). The initial FAC concentration and pH had a major influence on the removal process of CBZ during FAC photolysis, while temperature had a minor effect only. The combination of chlorination with natural sunlight could provide an effective approach for removal of CBZ and other contaminants during water treatment. Graphical abstract: Highlights: Chlorination of carbamazepine was dramatically enhanced by sunlight photolysis. These enhancements can be attributed to the in situ HO and O3 production. Oxidation products were formed from HO and O3 attack at the double bond of carbamazepine. Oxidation products did not cause any increase or decrease in toxicity to MARA microbial species. Initial chlorine dosage and pH had a major influence on the removal processes.